2010
DOI: 10.33584/jnzg.2010.72.2790
|View full text |Cite
|
Sign up to set email alerts
|

Herbage production from perennial ryegrass and tall fescue pastures under irrigation inthe Canterbury and Waikato regions of New Zealand

Abstract: The major limitation to perennial ryegrass-based systems is low soil moisture which reduces perennial ryegrass growth. irrigation can maintain adequate soil moisture levels for pasture growth, however, the associated cost requires high levels of forage water use efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Ryegrass and white clover are particular suitable in summer moist or irrigated pastures, where under the appropriate fertiliser and grazing management regime, they form a productive pasture of a high quality. In this experiment, annual herbage DM production was greater in the perennial ryegrass-based pastures (RG and HS) than TF-based pastures in the first but not second year, supporting similar results by Minneé et al (2010). Compared to perennial ryegrass, tall fescue pastures are more suitable and tolerant to hot, dry summer environments and may have higher growth rates (McCallum et al 1992).…”
Section: Dm Herbage Productionsupporting
confidence: 71%
“…Ryegrass and white clover are particular suitable in summer moist or irrigated pastures, where under the appropriate fertiliser and grazing management regime, they form a productive pasture of a high quality. In this experiment, annual herbage DM production was greater in the perennial ryegrass-based pastures (RG and HS) than TF-based pastures in the first but not second year, supporting similar results by Minneé et al (2010). Compared to perennial ryegrass, tall fescue pastures are more suitable and tolerant to hot, dry summer environments and may have higher growth rates (McCallum et al 1992).…”
Section: Dm Herbage Productionsupporting
confidence: 71%
“…Therefore, 'Advance' was more productive over the first 5 years, but both cultivars showed similar persistence after 6 years. Under partial irrigation in Canterbury, Minneé et al (2010) found that 'Advance' and 'Resolute' (another "Mediterranean" tall fescue) produced similar yields in the first 2 years, but that 'Resolute' had failed by the third year producing 3.8 t DM/ha less than 'Advance'. Further work is required to clarify differences in persistence between 'Advance' and 'Flecha' tall fescues.…”
Section: Resultsmentioning
confidence: 98%
“…Plant breeding of minor legumes and herbs has been a feature of plant breeding in New Zealand, largely initiated by government plant breeders. A number of these are now species of significant interest with private plant breeding companies, including grazingtolerant red clovers (Ford & Barrett 2011), plantain (Stewart 1996), chicory (Rumball 1986;Hare et al 1987), lucerne (Dunbier 1983), tall fescue (Easton & Pennell 1993;Easton et al 1994;Minnee et al 2010), cocksfoot (Dactylis glomerata) (Lolicato & Rumball 1994), grazing bromes (Bromus stamineus) (Stewart 1992), prairie grass (Bromus willdenowii) (Baars & Cranston 1977;Rys et al 1977), meadow fescue (Festuca pratensis) (Popay et al 2009), and forage brassica species (Lindsay et al 2007;Dumbleton et al 2012). However, there are many other forage species that fit minor ecological niches across New Zealand adding to resilience of pastures.…”
Section: Brief History Of Forage Plant Breeding In New Zealandmentioning
confidence: 99%